Phenotypic detection of extended-spectrum beta-lactamase in multidrug-resistant acinetobacter baumannii isolated in Fauji Foundation Hospital Rawalpindi - Asim Ali Shah; Yasir Ali; Ayesha Maqbool; Shahid Ahmad Abbasi (Journal of the Pakistan Medical Association, 2021)
Objective: To evaluate the phenotypic detection of extended-spectrum beta-lactamase in multidrug-resistant acinetobacter baumannii. Methods: The cross-sectional study was conducted at the Department of Microbiology, Fauji Foundation Hospital, Rawalpindi, Pakistan, from August 2018 to April 2019, after the ethical approval from the Institutional Review Committee. Consecutive Non- probability sampling technique was used, and comprised clinical specimens, including pus, blood, sputum, urine, tracheal tubes and canula double lumen, which were processed using standard protocols. Colonies of acinetobacter baumannii were identified by gram staining and Analytical Profile Index-20E kit. Combination disc method was used for the identification of extended-spectrum beta-lactamse. Clinical and Laboratory Standards Institute guidelines were used for antimicrobial susceptibility. Data was analysed using SPSS 22 and Sample size was calculated by using earlier study with 5 % margin of error and 95 % confidence level. Results: Of the 78 isolates, 58(74.4%) related to females and 20(25.6%) to males. There was no extended-spectrum beta-lactamse producer. Imipenem, meropenem, cefotaxime, ampicillin and ceftazidime showed 100% resistance, while colistin and polymyxin B were sensitive to all strains. The incidence rate was high in samples isolated from tracheal tubes 47(60.3%), followed by pus 21(26.9%). Age was not found to be a significant factor (p>0.05). Conclusion: Acinetobacter baumannii showed a high resistance to multiple drugs and was not confined to any specific age group. Colistin and polymyxin B were found to be better choices. Continuous...